The common agricultural policy: A policy evolving with the times (Bruselas Comisión de las Comunidades Europeas, 2004)
Contiene: Introduction -- A brief history of the CAP -- The CAP of tomorrow -- Funding -- Market management tools -- Single payment for farmers -- Rural development measures -- High standards, quality, safety -- The CAP and enlargement -- World trade issues -- The benefits of the CAP -- The CAPS aims in a nutshell
Keywords: DESARROLLO AGROPECUARIO; UNION EUROPEA; POLITICA AGRICOLA